4x+3=7x+3

Simple and best practice solution for 4x+3=7x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+3=7x+3 equation:


Simplifying
4x + 3 = 7x + 3

Reorder the terms:
3 + 4x = 7x + 3

Reorder the terms:
3 + 4x = 3 + 7x

Add '-3' to each side of the equation.
3 + -3 + 4x = 3 + -3 + 7x

Combine like terms: 3 + -3 = 0
0 + 4x = 3 + -3 + 7x
4x = 3 + -3 + 7x

Combine like terms: 3 + -3 = 0
4x = 0 + 7x
4x = 7x

Solving
4x = 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
4x + -7x = 7x + -7x

Combine like terms: 4x + -7x = -3x
-3x = 7x + -7x

Combine like terms: 7x + -7x = 0
-3x = 0

Divide each side by '-3'.
x = 0

Simplifying
x = 0

See similar equations:

| 16x^2+57x+49=x | | 3p^2-12q^2=0 | | 530=22-32+3x | | 7+4s-6=8s+5-3s | | 4s^2=s+1 | | -(8y+4)-(-7y-7)=-1 | | (2y-x+3z-13)-(4x+2-5y)+(6z+8)= | | 2.3-7x=-25.7 | | s^2=1+s(1-3s) | | (2bx+9x+4a)-(4bx-a)+(3b+a)= | | 6(3x-5)=3(6x+6) | | -2(q-4)=3q+12 | | 8(3a+7c)-6(2a+6c)= | | (2a^2b+7ab^2)+(3ab^2-2a^2b)= | | 8+2s-7=7s+3-4s | | -(3y+1)-(-2y-4)=-1 | | 3(x-2)(x+1)=0 | | -2y+6=20 | | 4z-7=5(5z-3) | | (5b-1)(6b-3)= | | 2x+20=304 | | -6x-(9y+(5x-(-2y-b))-(2b+a))= | | 2t^2-20t=0 | | 2(3v-1)+7v+7=5(v-6)+3v | | 304=s+20 | | 304=s+20w | | (4+w)(5w-8)=0 | | 30+9y=16y | | 5(w+2)-6(w+4)=0 | | (-6x-z)-(3y+(7x-(3z+8y+x)))= | | (5w+6)(5w-6)= | | -X+2x^2=0 |

Equations solver categories